Does media reputation affect properties of accounts payable?. Issue 1 (February 2015) - Van den Bogaerd, Machteld; Aerts, Walter
Abstract We examine economic benefits of a firm's corporate reputation by investigating the association between its media reputation and properties of trade payables in a sample of listed UK firms. Our results document a significant positive association between a firm's overall media reputation and both the level of its trade accounts payable and the number of days of trade credit received, suggesting that a favourable media reputation affects suppliers' credit risk perception of the firm and facilitates the firm's use of trade credit as a source of finance.